Cognitive Processes Unfold in a Social Context: A Review and Extension of Social Baseline Theory - Gross, Elizabeth B.; Medina-DeVilliers, Sara E. (Frontiers in Psychology, 2020)
Psychologists often assume that social and cognitive processes operate independently, an assumption that prompts research into how social context influences cognitive processes. We propose that social and cognitive processes are not necessarily separate, and that social context is innate to resource dependent cognitive processes. We review the research supporting social baseline theory, which argues that our default state in physiological, cognitive, and neural processing is to incorporate the relative costs and benefits of acting in our social environment. The review extends social baseline theory by applying social baseline theory to basic cognitive processes such as vision, memory, and joint action, incorporating individual differences into the theory, reviewing environmental influences on social baselines, and exploring the dynamic effects of social interactions. The theoretical and methodological implications of social baseline theory are discussed, and future research endeavors into social cognition should consider that cognitive processes are situated within our social environments.